Efektivitas Suscatin Terhadap Keharmonisan Keluarga Pada Kantor Urusan Agama Kecamatan Tubo Sendana (Studi Kasus Pasangan Di Bawah Umur Tahun 2020-2022) - Sunuwati, Sunuwati (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This study aims to evaluate the effectiveness of premarital courses in promoting family harmony at the Office of Religious Affairs in Tubo Sendana Subdistrict, focusing on underage couples during the period of 2020-2022. The research addresses two primary issues: the implementation of the premarital courses and the factors that support or hinder their execution. A qualitative research method with a field study approach was employed, where primary data were gathered through interviews with the local community and secondary data were collected from various literature sources. The findings indicate that the premarital courses were conducted in accordance with existing regulations; however, several obstacles were identified, including inadequate facilities and negative public perceptions regarding the importance of these courses. Supporting factors included the strategic location of the Office of Religious Affairs and the availability of competent instructors. Based on these findings, the study recommends improving the supporting facilities and intensifying public outreach to enhance understanding of the significance of premarital courses in fostering family harmony.